Outer Membrane Vesicles: Current Status and Future Direction of These Novel Vaccine Adjuvants - Tan, Kuang; Li, Ruizhen; Huang, Xiaotian; Liu, Qiong (Frontiers in Microbiology, 2018)
Adjuvants have been of great interest to vaccine formulation as immune-stimulators. Prior to the recent research in the field of immune stimulation, conventional adjuvants utilized for aluminum-based vaccinations dominated the adjuvant market. However, these conventional adjuvants have demonstrated obvious defects, including poor protective efficiency and potential side effects, which hindered their widespread circulation. Outer membrane vesicles (OMVs) naturally exist in gram-negative bacteria and are capable of engaging innate and adaptive immunity and possess intrinsic adjuvant capacity. They have shown tremendous potential for adjuvant application and have recently been successfully applied in various vaccine platforms. Adjuvants could be highly effective with the introduction of OMVs, providing complete immunity and with the benefits of low toxicity; further, OMVs might also be designed as an advanced mucosal delivery vehicle for use as a vaccine carrier. In this review, we discuss adjuvant development, and provide an overview of novel OMV adjuvants and delivery vehicles. We also suggest future directions for adjuvant research. Overall, we believe that OMV adjuvants would find high value in vaccine formulation in the future.